2005
DOI: 10.1515/cclm.2005.131
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of plasma homocysteine in postmenopausal women in Burkina Faso

Abstract: The elevated levels of homocysteine in the postmenopausal women of Burkina Faso must be viewed as a characteristic of older age and its metabolic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…Genotypic frequencies for this gene (78.6% AA, 19% AC, and 2.4% CC) in our study are also similar to those found in 20–45 years of age (79.27% AA, 17.07% AC, and 3.66% CC) in Burkina Faso [7]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Genotypic frequencies for this gene (78.6% AA, 19% AC, and 2.4% CC) in our study are also similar to those found in 20–45 years of age (79.27% AA, 17.07% AC, and 3.66% CC) in Burkina Faso [7]. …”
Section: Discussionsupporting
confidence: 88%
“…The genotypic frequencies found for the MTHFR C677T mutation are similar to those already reported in Burkina Faso [7]. Our results, however, differ from those reported in Sweden (46.3% 677CC, 43.4% 677CT, and 10.3% 677TT) in the mucosa of patients with colorectal cancer [13]; 28.6% 677CC, 44.9% 677CT, and 26.5% 677TT reported in patients with lymphoblastic leukemia in the Chinese population [17]; 51.4% 677CT, 41.4% 677CT, and 7.1% 677TT reported in Brazil in patients with chronic hepatitis C [14]; and 7.8% 677TT reported in children in the USA [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…L-Cys, the precursor of glutathione is degraded to Cys-gly, which again breaks into L-Cys and glycine. [9][10][11][12] Vitamin B 6 , B 9 and B 12 (cofactors) have very important roles in the metabolism of homocysteine. Decrease in B-vitamins caused due to dietary nutritional deficiency disturb the re-methylation process and influence the formation of t-Hcy and subsequent formation of cystathionine, L-Cys and GSH.…”
Section: Introductionmentioning
confidence: 99%